Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Explore in-depth answers to your questions from a knowledgeable community of experts across different fields. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

Multiple the binomials (simplify) (y-4)(y-8)

Sagot :

Given

[tex](y-4)(y-8)[/tex]

Simplify as shown below

[tex]\begin{gathered} (y-4)(y-8)=y(y-8)-4(y-8)=y^2-8y-4y+(-4)(-8)=y^2-12y+32 \\ \Rightarrow(y-4)(y-8)=y^2-12y+32 \end{gathered}[/tex]

The answer is y^2-12y+32